Dopamine and glutamate in individuals at high risk for psychosis: a meta‐analysis of in vivo imaging findings and their variability compared to controls. Issue 3 (9th September 2021) - McCutcheon, Robert A.; Merritt, Kate; Howes, Oliver D.
Abstract : Dopaminergic and glutamatergic dysfunction is believed to play a central role in the pathophysiology of schizophrenia. However, it is unclear if abnormalities predate the onset of schizophrenia in individuals at high clinical or genetic risk for the disorder. We systematically reviewed and meta‐analyzed studies that have used neuroimaging to investigate dopamine and glutamate function in individuals at increased clinical or genetic risk for psychosis. EMBASE, PsycINFO and Medline were searched form January 1, 1960 to November 26, 2020. Inclusion criteria were molecular imaging measures of striatal presynaptic dopaminergic function, striatal dopamine receptor availability, or glutamate function. Separate meta‐analyses were conducted for genetic high‐risk and clinical high‐risk individuals. We calculated standardized mean differences between high‐risk individuals and controls, and investigated whether the variability of these measures differed between the two groups. Forty‐eight eligible studies were identified, including 1, 288 high‐risk individuals and 1, 187 controls. Genetic high‐risk individuals showed evidence of increased thalamic glutamate + glutamine (Glx) concentrations (Hedges' g=0.36, 95% CI: 0.12‐0.61, p=0.003). There were no significant differences between high‐risk individuals and controls in striatal presynaptic dopaminergic function, striatal D2/D3 receptor availability, prefrontal cortex glutamate or Glx, hippocampal glutamate or Glx, or basal ganglia Glx. In the meta‐analysis of variability, genetic high‐risk individuals showed reduced variability of striatal D2/D3 receptor availability compared to controls (log coefficient of variation ratio, CVR=–0.24, 95% CI: –0.46 to –0.02, p=0.03). Meta‐regressions of publication year against effect size demonstrated that the magnitude of differences between clinical high‐risk individuals and controls in presynaptic dopaminergic function has decreased over time (estimate=–0.06, 95% CI: –0.11 to –0.007, p=0.025). Thus, other than thalamic glutamate concentrations, no neurochemical measures were significantly different between individuals at risk for psychosis and controls. There was also no evidence of increased variability of dopamine or glutamate measures in high‐risk individuals compared to controls. Significant heterogeneity, however, exists between studies, which does not allow to rule out the existence of clinically meaningful differences.